PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP BRAND IMAGE PRODUK INDOMIE PADA PT. INDOFOOD CBP SUKSES MAKMUR.TBK MAKASSAR - Muh. Fuad Randy (Jurnal Bisnis dan Kewirausahaan, 2017)
Marketing paradigm is now changed from a product-oriented into a brand-oriented. This research aims to know the existence of the influence between the Integrated Marketing Communiation (IMC) against the product Indomie Brand Image as well as knowing which variables are more dominant than in influencing the product Indomie Brand Image PT. Indofood CBP Sukses Makmur.Tbk Makassar. The method used in this study, quantitative research methods. Data collected through interviews and questionnaires. Data were analyzed with multiple linear regression analysis and hypothesis testing analysis. The results Showed the Integrated Marketing Communication (IMC) the which consists of advertising, sales promotion, public relations, personal selling, and direct, online and mobile marketing the positive and significant effect against the brand image on the product Indomie PT. Indofood CBP Sukses Makmur.Tbk Makassar. While on the test variable turned out to be partially personal selling, and direct, online and mobile marketing no effect Significantly to Brand Image on the product Indomie PT. Indofood CBP Sukses Makmur.Tbk Makassar. Furthermore the dominant variable is a variable of advertising where advertising influence greater than sales promotion and public relations against the Brand Image on the product Indomie PT. Indofood CBP Sukses Makmur.Tbk Makassar.